Characteristics and sources of trace elements in PM2.5 in two megacities in Sichuan Basin of southwest China. (November 2018) - Wang, Huanbo; Qiao, Baoqing; Zhang, Leiming; Yang, Fumo; Jiang, Xia
Abstract: To characterize major trace elements in PM2.5 and associated sources in two megacities, Chengdu (CD) and Chongqing (CQ), in Sichuan Basin of southwest China, daily PM2.5 samples were collected at one urban site in each city from October 2014 to July 2015 and were analyzed for their contents of thirteen trace elements including four crustal elements (Al, Ca, Fe, and Ti), eight trace metals (K, Cr, Zn, Cu, Mn, Pb, Ni, and V), and As. Multiple approaches including correlation analysis, enrichment factor, principal component analysis, and conditional probability function (CPF) were applied to identify potential sources of these elements. Most of the measured trace elements in Sichuan Basin were found to have lower concentrations than in the other regions of China. K and Fe were the most abundant elements at CD with an annual mean concentrations of 720 ± 357 and 456 ± 248 ng m −3, accounting for 34.6% and 21.9% of the total analyzed trace elements, respectively. Ca presented the highest concentration among all of the elements at CQ with annual mean of 824 ± 633 ng m −3 (29.1% of the total). Crustal elements had the highest concentrations in spring while heavy metals had distinct seasonal variations typically with the highest concentrations in winter and the lowest in summer. Ti and Al were identified to be primarily from soil while most of the analyzed heavy metals (Cr, Mn, Cu, Zn, Pb, Ni) and As were from anthropogenic sources associated with coal combustion, industrial emission from glassmaking production and iron/steel manufacturing, and non-exhaust vehicle emission. Graphical abstract: Image 1 Highlights: Trace elements in PM2.5 were measured in urban environments in Sichuan Basin. Source appointment analysis was conducted for trace elements. Glassmaking production was an importance source of heavy metals in Chengdu. Iron/steel and cement industry were important sources of K, Cr, and Ca in Chongqing. Abstract : We have conducted a compressive study to identify sources of major trace elements in Sichuan Basin.